PENERAPAN MODEL KOOPERATIF TIPE THINK PHAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS X MA MUHAMMADIYAH PEKANBARU - Utami, Nurul Putri; Natalina L, Mariani; Arnentis, Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The study was conducted in classes X MA Muhammadiyah Pekanbaru to determine the increase learning outcomes of students by implementing cooperative model type Think Phair Share (TPS). This research is a classroom action research conducted in this study is the learning outcomes that emphasizes on three areas, namely knowledge, attitudes and skills. Data were collected using test and observation sheet. The results showed learning outcomes in every sphere has increased. The cognitive value seen from the results of daily tests on the firsts cycle that 82,21 (enough category)is increased in the second cycle is 90,71 (good category). Students who complete the first cycle of 22 students (78,57%) and increased in the second cycle is 28 (100%). On average of attitudes value in the first cycle , namely 77,82 (less category)and increased the second cycle 90,72 (good category). Average of skills value in the first cycle, namely 86,50 (enough category) and increased in the second cycle is 91,50 (good category). It can be concluded that the application of cooperative model Think Phair share(TPS) can improve learning outcomes students class X MA Muhammadiyah Pekanbaru. The award of a debtor groups in the cycle of I for two great teams ( the great the rest of the team ) is the same as one group , and the super ( super the rest of the team ) four groups of .While in the case of the cycle of II the whole smeru team had managed to develop into the criteria for the super ( super ) the rest of the team.Key Words : Cooperative model Think Phair Share (TPS), Learning Outcomes